Geografia histórica, cidade e memória : narrativas que revelam a formação territorial de Itabatã (BA) - Dias, Maiara dos Santos (2019)
The urbanization process has been intensified in the last decades, associated, especially, with globalization and capitalist development. In this way, we can see the considerable growth of small urban centers, mostly based on the interests of capital, to